From Unit to Dose: A Machine Learning Approach for Precise Prediction of Hemoglobin and Iron Content in Individual Packed Red Blood Cell Units. Issue 36 (4th November 2022) - Epah, Jeremy; Gülec, Ilay; Winter, Stefan; Dörr, Johanna; Geisen, Christof; Haecker, Eva; Link, Dietmar; Schwab, Matthias; Seifried, Erhard; Schäfer, Richard
Abstract: Transfusion of packed red blood cells (pRBCs) saves lives, but iron overload limits survival of chronically transfused patients. Quality control methods, which involve entering pRBC units and removing them from the blood supply, reveal that hemoglobin (38.5–79.9 g) and heme iron (133.42–276.89 mg) vary substantially between pRBCs. Yet, neither hemoglobin nor iron content can be quantified for individual clinically used pRBCs leading to rules of thumb for pRBC transfusions. Keeping their integrity, the authors seek to predict hemoglobin/iron content of any given pRBC unit applying eight machine learning models on 6, 058 pRBCs. Based on thirteen features routinely collected during blood donation, production and quality control testing, the model with best trade‐off between performance and complexity in hemoglobin/iron content prediction is identified. Validation of this model in an independent cohort of 2637 pRBCs confirms an adjusted R 2 > 0.9 corresponding to a mean absolute prediction error of ≤1.43 g hemoglobin/4.96 mg iron (associated standard deviation: ≤1.13 g hemoglobin/3.92 mg iron). Such unprecedented precise prediction enables reliable pRBC dosing per pharmaceutically active agent, and monitoring iron uptake in patients and individual iron loss in donors. The model is implemented in a free open source web application to facilitate clinical application. Abstract : Hemoglobin and iron content vary substantially between packed red blood cell (pRBC) units, leading to rules of thumb for blood transfusions. Machine learning now allows to precisely predict hemoglobin and iron content of individual pRBC units, enabling for the first time reliable pRBC dosing per pharmaceutically active agent, and monitoring iron uptake in patients and individual iron loss in donors.